171k views
0 votes
Solve the eqaution 6 - 6x =5x - 9x -2.

2 Answers

4 votes

You want to get the variable, x, onto one side of the equation so you can solve for it.

6 - 6x = -4x - 2

Add 6x to both sides

Don’t actually use the brackets, it’s just to simplify

6 ( - 6x + 6x ) = (- 4x + 6x) - 2

6 = 2x - 2

Add 2 to both sides

6 + 2 = 2x (-2 + 2)

8 = 2x

Divide both sides by 2

8/2 = 2x/2

4 = x

User Andriy Drozdyuk
by
5.4k points
6 votes
Simplifying
6 + -6x = 5x + -9x + -2

Reorder the terms:
6 + -6x = -2 + 5x + -9x

Combine like terms: 5x + -9x = -4x
6 + -6x = -2 + -4x

Solving
6 + -6x = -2 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
6 + -6x + 4x = -2 + -4x + 4x

Combine like terms: -6x + 4x = -2x
6 + -2x = -2 + -4x + 4x

Combine like terms: -4x + 4x = 0
6 + -2x = -2 + 0
6 + -2x = -2

Add '-6' to each side of the equation.
6 + -6 + -2x = -2 + -6

Combine like terms: 6 + -6 = 0
0 + -2x = -2 + -6
-2x = -2 + -6

Combine like terms: -2 + -6 = -8
-2x = -8

Divide each side by '-2'.
x = 4

Simplifying
x = 4


I hope this helps!
User Dejo
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.